Heterogeneity of benefit finding in maintenance hemodialysis patients: a decision tree-based subgroup analysis of self-efficacy and social support - Fan, Yan; Tong, Tianci; Wang, Yiru; Gong, Yanlin; Wu, Jing; Chu, Jing (Frontiers in Psychiatry, 2025)
BackgroundBenefit finding (BF) improves quality of life in maintenance hemodialysis (MHD) patients, yet population heterogeneity remains understudied. This study explores how self-efficacy and social support jointly influence BF patterns and identifies distinct patient subgroups.MethodsThis multi-center cross-sectional study was conducted from April to September 2023 at five tertiary hospitals in Shanghai, China, enrolling 352 MHD patients. Data from the Benefit Finding Scale, General Self-Efficacy Scale, and Perceived Social Support Scale were used to construct a Classification and Regression Tree (CART) model employing five-fold cross-validation, with a maximum depth of 3 and a minimum leaf node size of 10%.ResultsThe CART model (R²=0.278) identified five distinct BF subgroups (p<0.001): Low Self-Efficacy Constrained Group, Psychological Resource Deficient Group, Internally Belief Driven Group, Balanced Resource Adaptation Group, and Resource Integrated Advantage Group, each characterized by unique combinations of self-efficacy and social support. Significant differences were observed among the subgroups in terms of gender(p=0.045), education level(p=0.010), and employment status(p=0.003).ConclusionBF levels in MHD patients demonstrated significant variations influenced by the combined effects of self-efficacy and social support. The decision tree model successfully identified patient subgroups with distinct psychological resource configurations. These findings provide a theoretical foundation for implementing stratified and personalized psychological interventions in clinical practice. Clinicians can identify and prioritize vulnerable patients who simultaneously lack self-efficacy and social support, offering them targeted positive psychological interventions that may potentially improve treatment adherence and long-term prognosis.